Exploring the Role of English Reading in Enhancing Vocabulary - Subroto, Gatot; Alias, Muhammad; Juhri, Muhammad; Juliardi, Juliardi; Syahputra, Muhammad Raihan Ihsan; Pratama, Irwin Harja (Langue (Journal of Language and Education), 2025)
Vocabulary development has an important role in English language learning, especially in supporting reading comprehension and oral communication. This research tries to explore the impact of reading English on vocabulary mastery among students and learners in informal housing environments. Using a quantitative descriptive approach, data were collected from 53 participants through a Likert-scale questionnaire distributed via Google Forms. The questionnaire examined four key variables: interest in reading, reading comfort, vocabulary improvement, and motivation. The findings indicate that most students show high interest and comfort in reading English texts. A significant majority agreed that reading helps them learn and retain new vocabulary. Additionally, reading activities were found to enhance students’ motivation to engage further with English learning. These results support existing literature that extensive reading positively influences vocabulary acquisition. Furthermore, the study highlights the importance of promoting English reading habits outside formal education environments. It is recommended that educators, parents, and communities provide accessible reading materials to foster vocabulary growth and language learning motivation among learners. By encouraging reading as a regular practice, even in informal settings, learners can develop a stronger foundation in vocabulary that benefits their overall English proficiency.